2018
DOI: 10.1021/acsnano.8b00304
|View full text |Cite
|
Sign up to set email alerts
|

Generalized 3D Printing of Graphene-Based Mixed-Dimensional Hybrid Aerogels

Abstract: Graphene-based mixed-dimensional materials hybridization is important for a myriad of applications. However, conventional manufacturing techniques face critical challenges in producing arbitrary geometries with programmable features, continuous interior networks, and multimaterials homogeneity. Here we propose a generalized three-dimensional (3D) printing methodology for graphene aerogels and graphene-based mixed-dimensional (2D + nD, where n is 0, 1, or 2) hybrid aerogels with complex architectures, by the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
210
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(211 citation statements)
references
References 57 publications
1
210
0
Order By: Relevance
“…It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…e) Ragone plot of the 3D GA/MnO 2 //SF‐3D GA device. The values reported for other supercapacitor devices (3D GA/MnO 2 SSC, laser‐scribed graphene electrochemical capacitor (LSG‐EC) SSC, carbide‐derived carbons (CDC)/TiC MSC, graphite/polyaniline (PANI) SSC, d‐Ti 3 C 2 SSC, TiN SSC, MnO 2 /carbon nanoparticles (CNPs) SSC, 3D GA SSC, 3D‐printed GA SSC, polypyrrole (PPy) SSC, MnO 2 /H‐TiO 2− x //C/H‐TiO 2− x ASC, Au/MnO 2 MSC, G/MnO 2 //G ASC, and MoO 3− x /PANI ASC,) are added for comparison. SSC: symmetric supercapacitor; MSC: micro‐supercapacitor.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Fan et al introduced a progressive cross‐linking scheme to print graphene hybrid aerogel on arbitrary surface and form ultra‐thick electrodes with highly interconnected 3D networks to provide sufficient ions and electron transport paths. This work can realize high areal capacitances in a confined area indicating tremendous potential applications …”
Section: Fabrication Methodsmentioning
confidence: 99%
“…In 2018, Tang et al reported the fabrication of graphene-based mixed-dimensional hybrid aerogels for the 3D printing of flexible MSCs. [153] By mixing MWCNTs, GO, glucono d-lactone, and urea together, interconnected hierarchical pores could be constructed by means of 3D printing. The MSCs delivered am aximum areal capacitance of 639 mF cm À2 at ac urrent density of 4mAcm À2 and maintained 90 %c apacitance after 10 000 GCD cycles at 40 mA cm À2 .T he strongly coupled mixed-metal chalcogenides could enhance the electrical/ionic conductivity and improve reversible capacity,a nd thus, were beneficial for electrochemical applications.…”
Section: Three-dimensional Mscsmentioning
confidence: 99%